2020
DOI: 10.1111/jfbc.13157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wheat, soybean, rice, and pea protein properties for effective applications in food products

Abstract: Pea and rice proteins are promising to substitute allergenic proteins, and increasingly, play important roles in the food industry because of their hypoallergenic characteristics and nutritional value. However, manufacturers generally provide limited functionality information on these proteins. Therefore, this study comprehensively compared functional properties of wheat, soybean, rice, and pea proteins for their industrial applications and illustrated correlation among various functionalities. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 49 publications
9
76
3
1
Order By: Relevance
“…RPC showed the best emulsifying capacity among the plant protein-based ingredients and the highest CS (Table 2). This is in contrast with the results by Zhao, Shen, Wu, Zhang, and Xu (2020), who reported a very low EAI for rice proteins in comparison with soybean and pea proteins, probably due to the very low solubility of their rice protein concentrate at pH 7. In fact, Mun, Shin, and Kim (2016) demonstrated that solubility of rice proteins depends on the rice cultivar used for the extraction and emulsifying properties are affected not only by protein solubility but also by other properties, such as the amino acid composition and the hydrophilic-lipophilic balance.…”
Section: Rice Protein Concentratecontrasting
confidence: 99%
See 1 more Smart Citation
“…RPC showed the best emulsifying capacity among the plant protein-based ingredients and the highest CS (Table 2). This is in contrast with the results by Zhao, Shen, Wu, Zhang, and Xu (2020), who reported a very low EAI for rice proteins in comparison with soybean and pea proteins, probably due to the very low solubility of their rice protein concentrate at pH 7. In fact, Mun, Shin, and Kim (2016) demonstrated that solubility of rice proteins depends on the rice cultivar used for the extraction and emulsifying properties are affected not only by protein solubility but also by other properties, such as the amino acid composition and the hydrophilic-lipophilic balance.…”
Section: Rice Protein Concentratecontrasting
confidence: 99%
“…RPC_F mix showed a density value significantly higher than that of REF (Table 4). Thus, it is presumable that the used rice proteins had low foaming capacity, as observed also by Zhao et al (2020) for a different commercial product, resulting in a denser ice cream mix. The significantly lower value of Brix degree was probably due to the interference of some RPC components during the analysis with the digital refractometer.…”
Section: Rice Protein Concentratementioning
confidence: 81%
“…Through incorporation into staple food, pea protein ingredients could offer opportunities to enhance the protein content in the diet while providing some functionality (binder, emulsifier, stabilizer or extender) to the formulation (Zhao, Shen, Wu, Zhang, & Xu, 2020). This section aims to provide a better understanding of the impacts of pea protein on array of products (bread, pasta, baked goods, snacks, meat products and beverage) as summarized in Table 2.…”
Section: Pea Protein Ingredients In Food and Beverages Applicationsmentioning
confidence: 99%
“…In turn, their solubility is increased as the system's pH moves away from the isoelectric point (Bessada, Barreira, & Oliveira, 2019;Karaca et al, 2011;Shevkani et al, 2019). Recently, Zhao, Shen, Wu, Zhang, and Xu (2020) studied the pH related solubility of distinct plant proteins, i.e., pea, soybean, wheat and rice. Their isoelectric point was estimated to be around pH 4-6, 4-5 and 6-7 for pea, soybean and wheat, respectively, at which protein precipitation was almost complete.…”
Section: Protein Solubilitymentioning
confidence: 99%